2008
DOI: 10.1038/onc.2008.56
|View full text |Cite
|
Sign up to set email alerts
|

Co-injection strategies to modify radiation sensitivity and tumor initiation in transgenic Zebrafish

Abstract: The zebrafish has emerged as a powerful genetic model of cancer, but has been limited by the use of stable transgenic approaches to induce disease. Here, a co-injection strategy is described that capitalizes on both the numbers of embryos that can be microinjected and the ability of transgenes to segregate together and exert synergistic effects in forming tumors. Using this mosaic transgenic approach, gene pathways involved in tumor initiation and radiation sensitivity have been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 20 publications
3
75
0
Order By: Relevance
“…These tumors were fluorescently labeled by co-injection of embryos with both an oncogene and fluorescent marker; because the DNA co-segregates, any cell expressing the oncogene will also express the fluorescent protein 17 . While fluorescence is recommended because it facilitates tracking of tumor growth without the need to sacrifice the animal and provides a straight-forward way to isolate tumor cells by FACS, it is possible to label tumor cells with antibodies to tumorspecific makers to facilitate their purification, though antibody staining in zebrafish may require optimization.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors were fluorescently labeled by co-injection of embryos with both an oncogene and fluorescent marker; because the DNA co-segregates, any cell expressing the oncogene will also express the fluorescent protein 17 . While fluorescence is recommended because it facilitates tracking of tumor growth without the need to sacrifice the animal and provides a straight-forward way to isolate tumor cells by FACS, it is possible to label tumor cells with antibodies to tumorspecific makers to facilitate their purification, though antibody staining in zebrafish may require optimization.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if the transgenic fish line overexpressing one of the candidate oncogenes is available (in our case, MYCN transgenic fish were developed), linearized transgenic DNA constructs containing other candidate genes can be injected into one-cell stage transgenic embryos to study their cooperation in tumorigenesis. Up to three transgene constructs can be coinjected and coexpressed in the primarily injected fish 31 ; thus, the interaction of candidate oncogenes in tumorigenesis can be assessed in the primarily injected fish. Please click here to view a larger version of this figure.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Thus far, this strategy has also been successfully applied in transgenic zebrafish to identify genes that suppress the activated RAS-induced initiation of rhabdomyosarcoma 31 and modify the radiation sensitivity of MYC-induced T-cell acute lymphoblastic leukemia 31 . Furthermore, Langenau et al, 15 have demonstrated that combining the coinjection approach with a heat-shock-inducible transgenic approach can induce transgene expression by heat shock in the primarily injected fish, which would be very useful in exploring the cooperative roles of oncogenes in tumor progression, as it permits gene expression to be turned on after the primary tumor is established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations